MENINGKATKAN MINAT BACA, KEMAMPUAN MEMAHAMI BACAAN, DAN BERPIKIR KRITIS SISWA MELALUI PENERAPAN SUSTAINED SILENT READING (SSR) DAN READING RESPONSE [IMPROVING STUDENTS' READING INTEREST, READING COMPREHENSION, AND CRITICAL THINKING THROUGH THE IMPLEMENTATION OF SUSTAINED SILENT READING (SSR) AND READING RESPONSE] - Listya Marmita (Jurnal Teropong Pendidikan, 2021)
Reading is one of the many skills which is taught in Indonesian language lessons. During lessons, students are usually asked to read a passage of text and answer comprehension questions. This makes reading activities less interesting. Since students are not able to find enjoyment in reading and they gain limited vocabulary. Consequently, students think that the Indonesian language is hard to master. Students’ reading interest, reading comprehension and critical thinking skills are low. This situation has urged the researcher to apply Sustained Silent Reading (SSR) and Reading Response as an alternative solution to the problem, as an act of improvement. Through the method of class action research, this research aims to describe the process of implementing Sustained Silent Reading (SSR) and Reading Response; analyse the development of students’ reading interest, reading comprehension and critical thinking skills; and also to describe the constrains during the implementation. Data has been collected with field notes, observation and scores of the students’ work using rubrics. The research consists of 3 cycles after which data was processed qualitatively and analysed descriptively. The research showed that students’ reading interest, comprehension and critical thinking skill had improved.